Effects of Different Green Teas on Obesity and Non-Alcoholic Fatty Liver Disease Induced by a High-Fat Diet in Mice - Zhou, Dan-Dan; Mao, Qian-Qian; Li, Bang-Yan; Saimaiti, Adila; Huang, Si-Yu; Xiong, Ruo-Gu; Shang, Ao; Luo, Min; Li, Hang-Yu; Gan, Ren-You; Li, Hua-Bin; Li, Sha (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) and obesity are serious public health problems. Green tea is widely consumed in the world and different green teas could possess different bioactivities. In this study, the effects of 10 selected green teas on obesity and NAFLD were evaluated and compared. The mice fed with a high-fat diet were intervened with green tea extract (200 mg/kg body weight) for 15 weeks. Most of these teas were first evaluated for their effects on obesity and NAFLD. The results showed that Selenium-Enriched Chaoqing Green Tea and Jieyang Chaoqing Tea showed the most prominent inhibition of obesity and body weight gains of mice in these two tea intervention groups and model groups were 5.3, 5.5, and 13.7 g, respectively. In addition, Jieyang Chaoqing Tea, Taiping Houkui Tea, and Selenium-Enriched Chaoqing Green Tea exerted the most notable effect on NAFLD, which was attributed to decreasing body weight, and lipid content and ameliorating oxidative stress. Furthermore, 13 phytochemicals were determined in these teas by high-performance liquid chromatography and the correlation analysis found that epigallocatechin gallate, gallocatechin, and epigallocatechin might contribute to the decrease of hepatic weight, while epicatechin might reduce oxidative stress. In general, several green teas could prevent the development of obesity and NAFLD and could be developed into functional foods. This study was also helpful for the public to select appropriate tea to prevent obesity and NAFLD.